Estimates of Tibial Shock Magnitude in Men and Women at the Start and End of a Military Drill Training Program. Issue 9 (26th March 2018) - Rice, Hannah M; Saunders, Samantha C; McGuire, Stephen J; O'Leary, Thomas J; Izard, Rachel M
Abstract: Introduction: Foot drill is a key component of military training and is characterized by frequent heel stamping, likely resulting in high tibial shock magnitudes. Higher tibial shock during running has previously been associated with risk of lower limb stress fractures, which are prevalent among military populations. Quantification of tibial shock during drill training is, therefore, warranted. This study aimed to provide estimates of tibial shock during military drill in British Army Basic training. The study also aimed to compare values between men and women, and to identify any differences between the first and final sessions of training. Materials and Methods: Tibial accelerometers were secured on the right medial, distal shank of 10 British Army recruits ( n = 5 men; n = 5 women) throughout a scheduled drill training session in week 1 and week 12 of basic military training. Peak positive accelerations, the average magnitude above given thresholds, and the rate at which each threshold was exceeded were quantified. Results: Mean (SD) peak positive acceleration was 20.8 (2.2) g across all sessions, which is considerably higher than values typically observed during high impact physical activity. Magnitudes of tibial shock were higher in men than women, and higher in week 12 compared with week 1 of training. Conclusions: This study provides the first estimates of tibial shock magnitude during military drill training in the field. The high values suggest that military drill is a demanding activity and this should be considered when developing and evaluating military training programs. Further exploration is required to understand the response of the lower limb to military drill training and the etiology of these responses in the development of lower limb stress fractures.